2013
DOI: 10.1002/eat.22153
|View full text |Cite
|
Sign up to set email alerts
|

A case of anorexia nervosa with comorbid Crohn's disease: Beneficial effects of anti‐TNF‐α therapy?

Abstract: This case report describes a 26-year-old woman affected by long-lasting anorexia nervosa (AN) and Crohn's disease. Worsening of the bowel illness led to the prescription of immunosuppressive therapy (biologic infliximab for 4 months, followed by adalimumab for 6 months) and referral to our Eating Disorders Unit. Although she initially demonstrated denial of her eating disorder, in a few months she gradually improved her weight and psychopathology. Crohn's disease can worsen AN by modifying hunger and energy ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 15 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…On the other hand, it has been shown that streptococcal infections may play a role in the development of a subtype of AN (PANDAS‐AN) . In addition, elevated proinflammatory cytokines, such as tumor necrosis factor (TNF)‐α, have been hypothesized to contribute to the development of AN . In our study, low use of antimicrobial medication in females with AN before the treatment suggests that the infection‐triggered inflammation does probably not play a major role in the development of AN in a larger female patient population.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…On the other hand, it has been shown that streptococcal infections may play a role in the development of a subtype of AN (PANDAS‐AN) . In addition, elevated proinflammatory cytokines, such as tumor necrosis factor (TNF)‐α, have been hypothesized to contribute to the development of AN . In our study, low use of antimicrobial medication in females with AN before the treatment suggests that the infection‐triggered inflammation does probably not play a major role in the development of AN in a larger female patient population.…”
Section: Discussionmentioning
confidence: 61%
“…23 In addition, elevated proinflammatory cytokines, such as tumor necrosis factor (TNF)-a, have been hypothesized to contribute to the development of AN. 41,42 In our study, low use of antimicrobial medication in females with AN before the treatment suggests that the infection-triggered inflammation does probably not play a major role in the development of AN in a larger female patient population. However, our results suggest that males with AN may differ from females in this respect.…”
Section: Discussionmentioning
confidence: 67%
“…Particularly interesting is TNF-α, a key cytokine in Crohn's disease, also known as cachexin due to its strong appetite suppressing and weight loss inducing effect. Interestingly, anecdotal evidence suggests positive effect of anti-TNF-α treatment in Crohn's disease on AN [45]. In celiac disease, both brain-reactive autoantibodies as well as high prevalence of mood disorders have been reported [3], [6].…”
Section: Discussionmentioning
confidence: 99%
“…12 Psychological stress may induce an inflammatory response with increased production of proinflammatory cytokines, and this inflammatory reaction may induce depression. 13 Furthermore, Solmi et al 14 reported that using anti TNF-a therapy to inflammatory bowel diseases, such as Crohn's disease, was associated with an improvement in the psychopathology of AN. 12 In regards to eating disorders, IL-6 is reported to enhance central leptin, and therefore, it is used in nutrient systems in the mouse model of eating disorders.…”
Section: Discussionmentioning
confidence: 99%